2018
DOI: 10.1080/09540121.2018.1465526
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between adverse neighborhood socioeconomic context and HIV continuum of care outcomes in a diverse HIV clinic cohort in the Southern United States

Abstract: Retention in care and viral suppression are critical to delaying HIV progression and reducing transmission. Neighborhood socioeconomic context (NSEC) may affect HIV care receipt. We therefore assessed NSEC's impact on retention and viral suppression in a diverse HIV clinical cohort. HIV-positive adults with ≥1 visit at the Vanderbilt Comprehensive Care Clinic and 5-digit ZIP code tabulation area (ZCTA) information between 2008 and 2012 contributed. NSEC z-score indices used neighborhood-level socioeconomic ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 37 publications
(63 reference statements)
2
20
0
Order By: Relevance
“…From such research we learned that unsuppressed HIV viral load is more common among PLHIV in the most socioeconomically disadvantaged neighborhoods. 10 When controlling for individual demographic characteristics, including age, gender, race, and income, such evidence emerges: PLHIV residing in neighborhoods with a higher proportion of poverty had 1.50 greater odds of having a CD4 cell count characteristic of an AIDS diagnosis (<200 cells/lL), PLHIV in neighborhoods with higher prevalence of unemployment were almost 50% less likely to have a current antiretroviral prescription, and PLHIV were more likely to report depressive symptoms if they resided in racially segregated neighborhoods. 11 Moreover, a measure of neighborhood disorder, an indicator of economic disadvantage, was associated with poorer antiretroviral treatment (ART) adherence.…”
mentioning
confidence: 99%
“…From such research we learned that unsuppressed HIV viral load is more common among PLHIV in the most socioeconomically disadvantaged neighborhoods. 10 When controlling for individual demographic characteristics, including age, gender, race, and income, such evidence emerges: PLHIV residing in neighborhoods with a higher proportion of poverty had 1.50 greater odds of having a CD4 cell count characteristic of an AIDS diagnosis (<200 cells/lL), PLHIV in neighborhoods with higher prevalence of unemployment were almost 50% less likely to have a current antiretroviral prescription, and PLHIV were more likely to report depressive symptoms if they resided in racially segregated neighborhoods. 11 Moreover, a measure of neighborhood disorder, an indicator of economic disadvantage, was associated with poorer antiretroviral treatment (ART) adherence.…”
mentioning
confidence: 99%
“…A rich body of data supports an association between community factors and important health outcomes (35)(36)(37). Much of this research has focused on poor socioeconomic status (SES) and other characteristics of neighborhood deprivation (18,35,37,38). One study set in TN found that individuals living in neighborhoods with the most adverse socioeconomic features were least likely to achieve virologic suppression (18).…”
Section: Discussionmentioning
confidence: 99%
“…Much of this research has focused on poor socioeconomic status (SES) and other characteristics of neighborhood deprivation (18,35,37,38). One study set in TN found that individuals living in neighborhoods with the most adverse socioeconomic features were least likely to achieve virologic suppression (18). Some authors hypothesize that the relationship between SES and health outcomes are mediated by distribution of stressors, which may be more prevalent in poorer neighborhoods and among racial and ethnic minorities (35,(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this framing allows us to see how the distribution of socioeconomic capital makes barriers to care such as cost and health insurance coverage even more pertinent in communities [ 4 , 42 , 43 ]. Similarly, a number of studies have found links between neighborhood socioeconomic context, resource availability, care engagement, and viral suppression [ 44 , 45 ]. For example, historically Black and resource-deprived neighborhoods are less likely to have an HIV care clinic nearby, therefore increasing travel time to appointments and reducing retention in care [ 46 ].…”
Section: Introductionmentioning
confidence: 99%